2019
DOI: 10.1063/1.5087804
|View full text |Cite
|
Sign up to set email alerts
|

Direct-current current transformer for the measurement of an electric propulsion ion beam

Abstract: An important task in the development of electric propulsion devices is ground-based testing. In order to characterize electric thrusters, their generated ion beams are regarded as figures of merit and have to be well-known and understood. We present an approach to measure DC ion beam currents generated by electric thrusters by means of an inductive direct-current current transformer. In contrast to commonly used devices like Faraday cups, this device can measure the beam current non-intrusively by means of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Given the rather high saturation field above 0.6 T, these Jiles–Atherton parameters have not been adopted, except for some tests, as described later. The magnetic characteristics adopted in this research were instead extracted by a manual fitting of the hysteresis curve reported in [ 44 ], in [ 27 , 54 ], starting from the parameters of Table 1 . In particular, the curve reported in Figure 4 of [ 44 ], the curve in Figure 1 of [ 27 ] and the curve in Figure 6 of [ 54 ] have been fitted.…”
Section: Modeling In Design Of Miniaturized Fsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the rather high saturation field above 0.6 T, these Jiles–Atherton parameters have not been adopted, except for some tests, as described later. The magnetic characteristics adopted in this research were instead extracted by a manual fitting of the hysteresis curve reported in [ 44 ], in [ 27 , 54 ], starting from the parameters of Table 1 . In particular, the curve reported in Figure 4 of [ 44 ], the curve in Figure 1 of [ 27 ] and the curve in Figure 6 of [ 54 ] have been fitted.…”
Section: Modeling In Design Of Miniaturized Fsmentioning
confidence: 99%
“…The magnetic characteristics adopted in this research were instead extracted by a manual fitting of the hysteresis curve reported in [ 44 ], in [ 27 , 54 ], starting from the parameters of Table 1 . In particular, the curve reported in Figure 4 of [ 44 ], the curve in Figure 1 of [ 27 ] and the curve in Figure 6 of [ 54 ] have been fitted. In the following, these will be referred to with the codes JA1, JA2, and JA3, respectively, for convenience.…”
Section: Modeling In Design Of Miniaturized Fsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric RF ion thruster (RIT-10, 37 extraction apertures), developed and built at Giessen University, Germany, was set up and operated following conventions and empirical data gained by the respective work group 2,14 . The radio-frequency generator (RFG) as well as the negative and positive high voltages (NHV and PHV) were operated as stated in Tab.…”
Section: A Thruster Setup / Beam Characterizationmentioning
confidence: 99%
“…To estimate the radial current density (J in A/m 2 ) for a 2D Gaussian beam distribution over radius r at a given distance z from the thruster exit plane, the following expression approximated for an ion beam expanding from a point source was used 14 :…”
Section: Numerical Approach a Beam Currentmentioning
confidence: 99%